The burden of injuries and illnesses in Para Athletes: A one-year prospective study of 102 para athletes across four sports - Madaleno, F. O.; Silva, A.; Verhagen, E.; Pinheiro, L. S. P.; Witvrouw, E.; Wezenbeek, E.; Lourenço, T. F.; de Mello, M. T.; Ocarino, J. M.; Resende, R. A. (Brazilian Journal of Physical Therapy, 2025)
Background Para athletes experience high prevalence, incidence, and burden of health problems related to sport. Objectives To assess the prevalence, incidence, severity, and burden of injuries and illnesses in Para athletes throughout one year and to compare the prevalence of these health conditions across four sports. Methods Data were collected from January to December 2022 at two Brazilian Paralympic Reference Centers. Para athletes from swimming, athletics, powerlifting, and taekwondo were included. The OSTRCsingle bondH2 Questionnaire was used to record injuries and illnesses weekly for one year. Injury and illness prevalence, incidence, severity scores, and burden were calculated. A one-way ANOVA compared the prevalence of health problems among the four sports. Results In total, 102 Para athletes participated in this study (77 males, 25 females). Six hundred and twelve health problems (453 injuries and 159 illnesses) were reported. The prevalence of injuries was 31.8 % (95 % CI: 28.2, 35.3), and the prevalence of illnesses was 7.9 % (95 % CI: 7.0, 8.9). Taekwondo had the highest prevalence of injuries (44.9 %). The mean incidence rate of sudden-onset injuries was 9.9 per 1000 athlete hours, with taekwondo also exhibiting the highest rates. Injuries to the shoulder complex, followed by the ankle and knee, had the greatest burdens. Powerlifting exhibited the highest burden of injuries. Conclusion During the one year season, Para athletes experienced high injury rates and burdens, with severe impacts observed especially in taekwondo and powerlifting. Para athletics had a high prevalence of illnesses. These findings emphasize the need to develop injury prevention strategies tailored to the specific characteristics of each sport.